CURRENT ISSUES USING THE GROUP DISCUSSION METHOD IN TEACHING PHILOLOGY STUDENTS (Konferensiyalar | Conferences, 2023)
In this article, the authors share their experience on the methods of conducting group discussions to increase the effectiveness of training, and about the free and prosperous world, the sanctity of the human factor, love, love - love in the lyrical works of Edgar Allan Poe, the great representative of modern American lyric literature. lyric works are analyzed.